Operational aircraft performance and flight test practices - Asselin, Mario, 1965- (AIAA education series., 2021)
"Operational Aircraft Performance and Flight Test Practices is intended to serve as a single source reference, from the basic theory to practical cases, for certification flight testing and operational performance monitoring. The first part of every subject begins with the development of the basic performance equations based on a given set of assumptions. Following this, deconstruction of the maneuver being analyzed to validate its components (create small flight test packages to validate models and expected airplane behavior) is conducted. Then, flight test considerations are discussed including required instrumentation, flight test risk and risk mitigation, data scatter, data reduction and presentation of the performance information to the flight crew. Several examples of flight test results help the reader better understand what they may be faced with when collecting data to create performance models"--